Leader-following consensus of nonlinear discrete-time multi-agent systems with limited bandwidth and switching topologies - Wu, Jia; Li, Huaqing; Han, Qi; Wang, Zheng (ISA transactions, 2020)
This paper considers the leader-following consensus problem of discrete-time nonlinear multi-agent systems over switching topologies with limited bandwidth. Through the encoding–decoding data, we design a distributed feedback control protocol which is closely associated with the connectivity of relevant channel at each time step. An adaptive communication mechanism is presented to ensure fewer bits of information transmission at each time step under the premise that the quantizer for encoding and decoding is not saturated. Although the nonlinear model over switching topologies introduces a cumulative error with respect to consensus error at previous time steps, the convergence rate of the system can be characterized. Through a rigorous convergence analysis, we illustrate that if the jointly connected condition of communication networks is satisfied, consensus issues will be resolved. A numerical simulation example shows that based on the designed distributed control law, all states of the follower agents are ultimately the same as the leader’s state. •Address the leader-following consensus problem over switching topologies.•Design control protocol on the basis of dynamic encoding–decoding scheme.•The designed quantizers are proved to be unsaturated.•Provide an explicit mathematic expression of quantization levels.•Achieve consensus with fewer bits of data for communication efficiency.